Factors associated with HIV infection are not the same for all women. Issue 2 (1st February 2002) - Boisson, E V; Rodrigues, L C
Abstract : Study objectives: To determine if factors associated with HIV infection vary between subpopulations of women resident in Great Britain. Design: Case-control analyses on already existing datasets. Setting: Great Britain. Participants: 317 cases selected from a MRC Collaborative Study of HIV Infection in Women and 3635 controls selected from a National Survey of Sexual Attitudes and Lifestyles. Main results: Factors associated with HIV infection varied among subpopulations of women. Among women heterosexually infected, factors associated with HIV infection were residence in London (odds ratio (OR) = 8.3; 95% confidence intervals (CI) 4.6 to 14.9), widowhood (OR = 47.6; CI 20.0 to 113.1), being black (OR = 25.2; CI 15.6 to 40.8) and particularly among white women, having 10 or more sexual partners (OR = 14.5; CI 5.1 to 41.3). Young age was important for black women heterosexually infected. Among women who shared needles, residence in London (OR = 19.0; CI 5.8 to 62.6) or Scotland (OR = 26.9; CI 8.0 to 90.4) and large numbers of sexual partners was important (OR = 19.6; CI 6.4 to 60.0); termination of pregnancy history was also important for those with fewer than 10 sexual partners (OR = 6.7; CI 3.4 to 13.1); and low social class was important for those with 10 or more sexual partners (OR = 4.1; CI 1.7 to 9.6). Conclusions: Factors vary in importance and significance of association with HIV infection in different subpopulations of women resident in Great Britain. This diversity is also likely to occur in other populations. It is important to identify these differences between subpopulations. Prevention and control policies and activities for HIV/AIDS cannot treat all women as if they were the same.